Peningkatan Pelayanan Dinas Pendidikan Dayah Kabupaten Aceh Barat Melalui Bahasa Komunikasi Berdasarkan Al-Qur’an dan Hadits - Fazri, Anhar; Zuhri, Al; Faisal, Muhammad; Juliani, Reni; Maulina, Putri; Fadillah, Haris; Dewi, Zuwidah; Maulida, Desi; Ilhamsyah, Fadhil (Universitas Teuku Umar, 2022)
Language is an important element in communicating both individually and in social groups that exist in society, especially in public services such as the Dayah Education Office of West Aceh Regency, as a public service body requires the use of good and correct language, especially in Aceh where the majority of the people adhere to Islam and of course can refer to the Koran and Hadith. The method used in this community service is in the form of counseling and socialization by using a discussion system for anything that has not been understood. In this service activity, many errors were found in public services, especially in the use of communication language used by employees and staff at the Dayah Education Office of West Aceh Regency, with this counseling, as well as learning to improve better services, especially in the use of communication languages based on the Qur'an and Hadith. The use of appropriate and good language will also affect the image of a public institution, because the people who are served will feel comfortable and appreciated.